KONFLIK KEWENANGAN BADAN PENGUSAHA BATAM DENGAN PEMERINTAH KOTA BATAM - Oktahade, Satria; Hospita, Wira; Yani, Ren (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to describe the conflict of power in the Batam free trade zone (FTZ) area. After the issuance of Law Number 53 of 1999 concerning Regional Government, the impact on the status of Batam City became the City Government of Batam. The positive effects that occur, the Batam region has two bodies that have authority in its management, namely Batam City Government to carry out the functions of government and development by involving the Batam Authority Agency (BP Batam). The dualism of management in the Batam area has resulted in a conflict of authority between BP Batam and Batam City Government, resulting in a tug of interest between political actors who have interests in the Batam area, ranging from global level, national level to local level which influence each other.